Five-Year Mortality After Transient Ischemic Attack: Focus on Cardiometabolic Comorbidity and Hospital Readmission. Issue 3 (March 2018) - Yousufuddin, Mohammed; Young, Nathan; Keenan, Lawrence; Olson, Tammy; Shultz, Jessica; Doyle, Taylor; Ahmmad, Eimad M.; Arumaithurai, Kogulavadanan; Takahashi, Paul; Murad, Mohammad Hassan
Abstract : Background and Purpose—: We aimed at providing estimates of mortality associated with cardiometabolic comorbidity and incident readmission from cardiometabolic as compared with noncardiometabolic conditions after a first transient ischemic attack. Methods—: Between 2000 and 2015, patients hospitalized for a first transient ischemic attack were examined for cardiometabolic comorbidities (diabetes mellitus, coronary artery disease, heart failure, and atrial fibrillation), 5-year incident hospitalization, and time to death. Results—: Of 251 patients with transient ischemic attack, 134 (53%) had at least 1 and 55 (22%) had at least 2 cardiometabolic conditions. By 5 years, 491 readmissions (134 [27%] cardiometabolic and 357 [73%] noncardiometabolic) and 75 deaths (27 [36%] cardiometabolic and 47 [64%] noncardiometabolic) were observed. Mortality was increased with any concurrent cardiometabolic comorbidity (hazard ratio, 1.89; 95% confidence interval, 1.17–3.03; P =0.0089) with multiplicative mortality risk from a combination of coronary artery disease and heart failure. Each hospitalization was associated with a 1.5-fold risk of death (95% confidence interval, 1.37–1.64; P <0.0001). Risk of cardiometabolic and noncardiometabolic mortality was correlated with the corresponding category-specific readmission. Conclusions—: Among patients hospitalized for first transient ischemic attack, 5-year mortality is associated with concurrent cardiometabolic comorbidity and rates of subsequent hospitalization. Abstract : Supplemental Digital Content is available in the text.